Efektivitas Penggunaan Media Pembelajaran Permainan Ludo Kimia Berbasis Chemo-Edutainment (CET) pada Materi Struktur Atom terhadap Hasil Belajar Siswa Kelas X SMA N 3 Padang - Annisa Rezky Fadillah; Iswendi Iswendi (Edukimia, 2019)
This study aimed to reveal the effectivity of the use an instructional media of ludo game based on Chemo Edutainment for Atomic Structure toward 10th students achievement. The type of this research was Quasi-Experimental Research with Non-Equivalent Control Group Design. The samples was chosen by purposive-sampling which result the experimental class and the control class. Then it can be concluded that the use of ludo game based on Chemo-Edutainment for Atomic Structure effective to increase 10th students achievement from SMA N 3 Padang